From Social Values to P‐Values: The Social Epistemology of the Intergovernmental Panel on Climate Change. Issue 2 (8th February 2016) - John, Stephen
Abstract: In this article I ask two questions prompted by the phenomenon of 'politically patterned' climate change denial. First, can an individual's political commitments provide her with good reasons not to defer to cognitive experts' testimony? Building on work in philosophy of science on inductive risk, I argue they can. Second, can an individual's political commitments provide her with good reasons not to defer to the Intergovernmental Panel on Climate Change's testimony? I argue that they cannot (at least, in the way identified in the first part of the article), because of the high epistemic standards which govern that body's assertions. The conclusion discusses the theoretical and practical implications of my arguments.